Participation, capacity building, empowerment and socio-economic well-being among Indian community through Mykasih entrepreneurship program in Kuala Lumpur, Malaysia - Dass, Mahaganapathy (2015)
The main purpose of this study is to holistically understand the factors influencing the socio-economic well-being of the Indian community in the urban areas of Kuala Lumpur, Malaysia. The socio-economic well-being effectiveness is tested by analyzing community development domains and MyKasih Program run by a Non-governmental Organization. There is no recent study to test effectiveness of any governmental or NGO's socio-economic well-being efforts on this minority community. This study utilized a quantitative approach supported by qualitative data. Quantitative approach was used to address the main objective of this study which is to derive regression model, while qualitative approach was utilized to understand the issues and to support the development of study instrument. The community also revealed that the scarcity of resources especially financial support is a big threat for poverty eradication. The influence of the community development and MyKasih Organization on achieving poverty eradication was tested using multiple regression analysis to identify the predictors. The findings of the multiple regressions show that five variables can be significant in predicting the urban poverty eradication; motivation, participation, empowerment, capacity building and entrepreneurship skills. The result of the study also does not contradict the empowerment theory, which says that people, who are empowered, will be free of poverty. The Indian people involved directly in the MyKasih programs tended to have positive perceptions of self-development, because they directly received economic benefits from small business and job involvement. Although the results show no significant contradiction with culture of poverty theory,which states that it is the marginalisation of the poor urban community through systematic implementation of government policies and mechanisms that influence its socio-economic well-being. The outcome of this study can be treated as an important branch of minority poverty eradication through empowerment within the scope of the community participation.